Influence of Occupational Stress and Demographic Factors as Predictors of Mental Health of Federal Road Safety Corps Personnelin Benue State Sector Command - Zakariah, Danladi; Ihaji, Elvis O.; Anhange, Samuel T. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
This study Investigated Occupational Stress and Demographic Factors as predictors of Mental Health of Federal Road Safety Corps Personnel in Benue State Sector Command. The study employed a cross-sectional survey design. A total of 232 Personnel consisting of 169(72.8%) males and 63(27.2%) females with ages ranging from 20-58 years (Mean age-36.30, SD- 8.34) were used for the study. The Occupational Stress Index (OSI) and Mental Health Inventory (MHI) were used for data collection. Statistical Analysis involved the use of Multiple Linear Regression and Univariate Analysis. The study adopted Statistical package for the Social Science (SPSS) version twenty-three (23) for data Analysis. The findings of the study showed that there was significant negative influence of Occupational Stress on Mental Health of Federal Road Safety Corps Personnel in Benue State Sector Command [R=-.422, R2=.178, F(4,228)=13.541, p<.05]. The findings of the study also revealed that there was no significant sex different on Mental Health of Federal Road Safety Corps Personnel in Benue State Sector Command F (2, 230) =.105, p>.05). There was no significant Main and Interaction Effect of Sex and Cadre on Mental Health of Federal Road Safety Corps personnel in Benue State Sector Command F (5, 228) =.105, p>.05). It was therefore recommended that the management of Federal Road Safety Corps in Benue State Sector Command should initiate policies and measures to improve Mental Health of Federal Road Safety Corps Personnel in Benue State Sector Command. It was also recommended that the management of Federal Road Safety Corps should pay serious attention to strenuous working condition, role overload, role ambiguity and role conflict by improving the workingconditions and reducing the workload of Federal Road Safety Corps personnel to enhance their Mental Health.